2016
DOI: 10.1111/ijsa.12148
|View full text |Cite
|
Sign up to set email alerts
|

Applicant Reactions to Selection Methods in China

Abstract: APPLICANT REACTIONS IN CHINA 2This study examines applicant reactions to ten popular selection methods in China.Using a sample of 294 graduates we found that Chinese applicants' reactions were highly favorable for work sample tests, interviews, and written ability tests, whereas Guanxi (i.e., relying on personal contacts when applying for a job) and graphology were perceived as the least favorable selection methods. Guanxi was also perceived as significantly less fair method compared to all others on all seven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…In response, there has also been an increasing focus on applicant reactions across countries, with dozens of studies examining similarities and differences in applicant reactions to popular methods comprising selection procedures. Although the North American context still prevails, there has been considerable growth in research in other countries, particularly within Europe (e.g., Anderson & Witvliet, 2008; Bertolino & Steiner, 2007; Hülsheger & Anderson, 2009; Konradt et al, 2017; Nikolaou & Judge, 2007), the Middle East (e.g., Anderson, Ahmed, & Costa, 2012), and Asia (e.g., Gamliel & Peer, 2009; Hoang, Truxillo, Erdogan, & Bauer, 2012; Liu, Potočnik, & Anderson, 2016). In fact, since the turn of the millennium, studies have been conducted in more than 30 countries worldwide (Walsh, Tuller, Barnes-Farrell, & Matthews, 2010).…”
Section: Addressing the “What’s New?” Question: An Updated Model Of A...mentioning
confidence: 99%
“…In response, there has also been an increasing focus on applicant reactions across countries, with dozens of studies examining similarities and differences in applicant reactions to popular methods comprising selection procedures. Although the North American context still prevails, there has been considerable growth in research in other countries, particularly within Europe (e.g., Anderson & Witvliet, 2008; Bertolino & Steiner, 2007; Hülsheger & Anderson, 2009; Konradt et al, 2017; Nikolaou & Judge, 2007), the Middle East (e.g., Anderson, Ahmed, & Costa, 2012), and Asia (e.g., Gamliel & Peer, 2009; Hoang, Truxillo, Erdogan, & Bauer, 2012; Liu, Potočnik, & Anderson, 2016). In fact, since the turn of the millennium, studies have been conducted in more than 30 countries worldwide (Walsh, Tuller, Barnes-Farrell, & Matthews, 2010).…”
Section: Addressing the “What’s New?” Question: An Updated Model Of A...mentioning
confidence: 99%
“…Recent research has also shown that the FFM predicts occupational attainment, expatriate cross-cultural adjustment and outcomes, creativity and innovation, and counterproductive behaviors at work (AlDosiry, Alkhadher, AlAqraa, & Anderson, 2016;Costa, Páez, Sánchez, Garaigordobil, & Gondim, 2015;Gilar, De Haro, & Castejón, 2015;Raman, Sambasiva, & Kumar, 2016;Salgado & Bastida, 2017). Moreover, research on applicant reactions has shown that personality inventories are well rated across the world (Aguado, Rico, Rubio, & Fernandez, 2016;Anderson, Ahmed, & Costa, 2012;Anderson, Salgado, & Hülsheger, 2010;Liu, Potocnik, & Anderson, 2016;Snyder & Shahani-Denning, 2012).…”
mentioning
confidence: 99%
“…Chinese job seekers might be less critical about the fairness and job‐relevance of information employers can find on social media than their North American counterparts. These findings should also be interpreted in relation to prior work on applicant reactions in China, showing particularly positive views of work sample tests, interviews, or ability tests but more negative views of resumes or Guanxi —that is, relying on personal contacts (Liu et al, 2016). Cybervetting might thus be considered similar to those latter selection methods by Chinese job seekers.…”
Section: Discussionmentioning
confidence: 89%